Linguistic politics in Argentina: the survival of the Quichua Santiagueño (Gestionar: revista de empresa y gobierno, 2022)
Every language is an effective instrument to develop knowledge of the world, languages not only allow us to create our own world of ideas and concepts, but also through it we can communicate with others. It is estimated that there are around 300 aboriginal languages that are at risk of disappearing in Latin America, language policies (in some cases non-existent) should protect this cultural heritage.In the Latin American region, the aboriginal language that has a greater number of speakers is Quechua, with approximately 10,000,000, which are geographically distributed between Ecuador, Peru, Bolivia and Argentina. This work relates the linguistic policies in Argentina, their planning and concrete use in the period from the mid-19th century to the 20th century.
Keywords: linguistic policies; quichua; aboriginal languages